Assessing the influence of CCAFS’ climate data and tools: findings from an Outcome Harvesting evaluation - Rassmann, Kornelia; Schuetz, Tonya; Thornton, Philip K.; Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) integrates climate change research across all CGIAR Research Centres and Research Programs. Some of CCAFS’ work since 2010 has involved the development of high quality, accessible and easy-to-use climate data and tools. With an increased focus on achieving development outcomes influenced by such data and tools, a study was carried out starting in 2016 to evaluate the development effectiveness of some of CCAFS’ climate products: the GCM Climate Portal, MarkSimGCM, and the Climate Analogues tool (Box 1). The study was designed to explore whether use of these three products has led to development outcomes, and if so, what type of changes have been observed and how exactly the products have contributed to such changes. Outcomes here are defined as behavioural changes in individuals, groups or institutions doing something differently with respect to climate-change-related knowledge, attitude, capacity, policy or practice. Outcome Harvesting (Box 2) was used for the evaluation, along with some elements from Impact Pathways thinking (Douthwaite et al. 2008) and Contribution Analysis (Mayne 2008). We started the harvest by collecting outcome leads from project documents and an online survey. These leads provided the basis for selecting those cases that appeared promising to be turned into SMART outcomes (Box 3). A majority (70%) of the 30 cases investigated that employed CCAFS’ climate products were new in the sense that they were not directly related to the CCAFS program. Results from the survey indicated that the data and tools frequently were employed in countries not directly targeted by the CCAFS program and that users often discovered the tools via web search. These observations suggest strongly that CCAFS’ climate data and tools are widely used even without specific promotion, which is consistent with CCAFS’ mandate as a provider of international public goods (IPGs). After email exchanges and phone interviews, we identified a total of 14 cases with a plausible linkage to one of the tools and sufficiently detailed information to qualify as SMART outcomes (Box 4). Of these 14 SMART outcomes, eight related to the GCM Climate Portal and six to the use of the Climate Analogues tool. We found several MarkSimGCM leads, but no SMART outcomes at this stage. One SMART outcome was developed into an extended outcome story (“Farms of the Future, Africa”, Box 5) and one (“Seeds for Needs, India”, Box 6) was unpacked in considerable detail.